Occurrence and distribution of antibiotic resistance genes in Elymus nutans silage from different altitudes on the Qinghai–Tibetan Plateau - Zhang, Xia; Xu, Dongmei; Su, Rina; Li, Fuhou; Chen, Hu; Jia, Mengya; Chen, Mengyan; Guo, Xusheng (Frontiers in Microbiology, 2025)
IntroductionAntibiotic resistance genes (ARGs) and antibiotic-resistant bacteria (ARB) have attracted more attentions in fermented feed recently. However, little information is available on the occurrence and distribution of ARGs in ensiled forages in the alpine region of the Qinghai-Tibetan plateau (QTP) with an extremely harsh environment.MethodsThe study investigated the distribution and spread mechanism of ARB and ARGs in Elymus nutans silage along 2600 m (low), 3600 m (medium) and 4600 m (high) altitude in the QTP.ResultsThe major ARG types in Elymus nutans silage were multidrug, aminoglycoside, bacitracin, beta-lactam and polymyxin, while tnpA and IS91 were the dominant mobile genetic elements (MGEs) subtypes in the Elymus nutans silage. The dominant ARGs were mainly carried by Pantoea, Enterobacter, Serratia, and Lelliottia. Although altitudinal gradient had no influence on the diversity or abundance of other ARGs and MGEs in the Elymus nutans silage (p > 0.05), the network co-occurrence patterns among ARGs, MGEs, and bacteria in high-altitude silage were more complex than that in low- and medium-altitude silages. The dominant clinical ARGs in the alpine silage were bacA and acrF, and the abundance of clinical ARGs decreased with prolonged fermentation time.DiscussionThis study provides important data on the status of ARGs in ensiled forage from the alpine region of the QTP.